Does the point (–3, 4) satisfy the equation y = –2x + 5? Yes Or No
1 answer:
Answer:
No
Step-by-step explanation:
y = -2x + 5
4 = -2(-3) + 5 - Substitute both x and y
4 = 6 + 5 - Simplify
4 ≠ 11
Hence, no, (-3, 4) doesn't statify the equation y = -2x + 5
You might be interested in
(2x^3-6x-4)/x if your simplifying that's the answer
Answer:
parallel: -1
y - 7 = -(x + 1)
y - 7 = -x - 1
y = -x + 6
Step-by-step explanation:
Assuming angle F is 68°, angle H will be
.. 360° -2*102° -68° = 88° . . . . . . . . selection B
Answer:
3
Step-by-step explanation:
6/2=3
six halves of cookies put the halves into pairs and you get 3
Answer:
y = 65x
Step-by-step explanation: